Highly efficient Er–Yb codoped double-clad fiber amplifier with an Yb-band resonant cavity. (10th January 2017) - Han, Qun; Yao, Yunzhi; Tang, Xiaoyun; Chen, Yaofei; Yan, Wenchuan; Liu, Tiegen; Song, Huiling
Abstract: A high-power Er–Yb codoped fiber amplifier (EYDFA) with an Yb-band resonant cavity is investigated. By introducing a linear resonant cavity formed by a pair of high-reflection double-clad fiber Bragg gratings, the Yb-ASE problem of high-power pumped EYDFAs can be resolved and the efficiency of the amplifier can be notably improved. At a pump power of 17 W, an output power of 7.25 W was experimentally achieved. The pump conversion efficiency and slope efficiency relative to the applied pump power are 42.6% and 45.6%, respectively. Moreover, due to the gain-clamping effect of the Yb cavity, the gain flatness of the amplifier is also evidently improved.